Solar Energy and Technology. Wörterbuch Deutsch-Englisch - Mijic, Goran (Solar Energy and Technology ;, 2016)
This comprehensive collection provides an unprecedented extensive bilingual dictionary on the subject of solar energy and helps users understand all the terms, abbreviations, phrases, and synonyms of solar energy and technology. Over 8000 entries also include subjects like solar infrastructures, components and other alternative energy technologies due to recent solar hybrid technology developments. See also: Vol. 2, the accompanying encyclopedia.